Hubungan Aktivitas Fisik dan Kualitas Tidur dengan Kejadian Hipertensi pada Lansia di Wilayah Kerja Puskesmas Matiti Kecamatan Doloksanggul Tahun 2025: Penelitian - Debora Sianipar; Jemadi; Rahayu Lubis; Rusmalawaty (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Hypertension is a common non-communicable disease in the community. A preliminary survey in the working area of Matiti Public Health Center, Doloksanggul District, found that 14 out of 20 older adults (70%) had hypertension, most of whom had low physical activity and poor sleep quality. This study aimed to determine the relationship between physical activity and sleep quality with hypertension among older adults, using a cross-sectional design with 99 purposively selected samples. Data were collected through interviews, questionnaires, and medical records, and analyzed using univariate and bivariate (Chi-square) methods. The prevalence of hypertension was 66.7%, with the highest proportion among those aged 61–65 years (46.5%), females (64.6%), high school education level (67.7%), farmers (73.7%), heavy physical activity (48.5%), and poor sleep quality (78.8%). Results showed a significant relationship between physical activity (p=0.042) and sleep quality (p=0.004) with hypertension. Promotive and preventive efforts are recommended to encourage a healthy lifestyle and increase older adults’ participation in Posbindu PTM, Prolanis, and Posyandu Lansia activities.